Breast density and impacts on health - Cruwys, Cheryl (Ecancermedicalscience, 2017)
The World Health Organization states ‘Early detection in order to improve breast cancer outcome and survival remains the cornerstone of breast cancer control’ [WHO (World Health Organization) (2017) Breast cancer: prevention and control Available from: http://www.who.int/cancer/detection/breastcancer/en/]. Breast Density Matters UK is a non-profit breast cancer organization. The organization’s mission is to educate about breast density and its screening and risk implications with the goal of achieving the earliest stage diagnosis possible for women with dense breasts. This educational mission is endorsed by breast imaging experts worldwide [Berg WA (2015–2017) Dense Breast-info Inc Available from: http://densebreast-info.org/about.aspx].